Czy diakon może w Polsce zgodnie z przepisami Kościoła łacińskiego asystować jako świadek urzędowy przy zawarciu małżeństwa w zwykłych okolicznościach? - Jakubiak, Tomasz (Ius Matrimoniale, 2016)
According to the belief prevailing in Poland that the deacon cannot assist at the marriage, the author enquires whether the practice of blessing marriages only by the priests is consistent with the law of the Roman Catholic Church. In his discussion, the author goes back to the norms written in the Second Vatican Council constitution Lumen Gentium and the Apostolic Letter of Pope Paul VI Sacrum Diaconatus Ordinem – consisting the basis of legislation regulating the considered matter. Subsequently, applying the general norms of the code of Canon Law about the collisions of law, he is answering a question about the value of the documents released by the Apostolic See and Polish Bishop’s Conference since 1983. In conclusion, the author notes that if, contrary to the cited arguments, someone would still insist that the deacon, beyond the delegation needs a specific consent of the local ordinary, it should be noted that in this case it is a doubt about the lawand such law do not oblige.